Land use changes in suburban areas – case study of Lublin - Mariola, Ferenc (Acta Agraria Debreceniensis, 2012)
The main reason to analyzing the space structure in the Lublin area is to determine the direction and pace of suburbanization in municipalities adjacent to Lublin, distinction factors and motives of population movements to the suburbs, complain rural-urban interaction and multifunctionality of land use. Housing development over the years was accompanied by confusion in planning documents and the law. Changes in regulations on land use in 1994 and 2003 in Poland additionally deepened the negative situation. Local authorities failed to control the spontaneous process of suburbanization, which adversely affected not only the spatial structure of municipalities, but also on local relationship, landscape, land use and the former urban systems. The result are long-term problems associated with incompatibility rural areas to support a growing number of residents, such as failure of the social and technical infrastructure.